High-order above-threshold ionization and high-order harmonic generation of diatomic molecules - Gazibegović-Busuladžić, Azra; Hasović, Elvedin; Odžak, Senad; Busuladžić, Mustafa; Milošević, B. Dejan (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2012)
We investigate high-order above-threshold ionization (HATI) and high-order harmonic generation (HHG) of diatomic molecules having different symmetries by a strong laser field using modified molecular strong-field approximation. We present our results for N2, O2, H2, and Ar2 molecules. Their initial highest occupied molecular orbitals are characterized by 3σg, 1πg, 1σg, and 5σu symmetry, respectively. By analyzing HATI and HHG spectra for different molecular orientation with respect to the laser polarization axis, and for different values of the electron or photon energies and electron emission angle, we are able to draw some conclusions about the molecular structure. The most noticeable feature of all molecular spectra is the existence of minima that are absent in the atomic case.